2014
DOI: 10.3892/mmr.2014.2260
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-25 promotes osteosarcoma cell proliferation by targeting the cell-cycle inhibitor p27

Abstract: An increasing body of evidence indicates that microRNAs (miRNAs), a class of small non‑coding RNAs, are often aberrantly expressed in human osteosarcoma. This study aimed to investigate the effects of miR‑25 and to identify its potential target genes in osteosarcoma (OS) cells. First, the expression of miR‑25 was detected by reverse transcription‑quantitative polymerase chain reaction (RT-qPCR), which revealed a significant upregulation of miR‑25 in osteosarcoma tissues compared to the adjacent healthy tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…One of the 2 studies reported that miR-25 was transfected into OS cells directly [49]. This study confirmed that miR-25 was frequently over-expressed in OS, and up-regulation of miR-25 promoted cell proliferation in vitro and tumor growth in a xenograftmouse model.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…One of the 2 studies reported that miR-25 was transfected into OS cells directly [49]. This study confirmed that miR-25 was frequently over-expressed in OS, and up-regulation of miR-25 promoted cell proliferation in vitro and tumor growth in a xenograftmouse model.…”
Section: Resultssupporting
confidence: 60%
“…Four of the 25 studies reported that miRNAs functions as onco-miRNAs in OS [34, 49-51]. A total of 26 mice in the intervention arm and 36 in the control arm were included.…”
Section: Resultsmentioning
confidence: 99%
“…Although several miRNAs have been found to be deregulated in osteosarcoma cells and tissues, the exact mechanism by how miRNA regulated the tumorigenesis is still not fully elucidated [31][32][33][34]. Our study showed that miR-423-5p expression was decreased in osteosarcoma tissues and cell lines.…”
Section: Discussionmentioning
confidence: 56%
“…and Wang et al . revealed that the expression of p27 was negatively regulated by miR-802 and miR-254041, thus illustrating that p27 might be regulated by several miRNAs simultaneously in OS. Together, our data indicate that miR-199a-5p as an oncogenic miRNA can remarkably promote OS progression by targeting both PIAS3 and p27.…”
Section: Discussionmentioning
confidence: 92%